The prevalence and in-hospital mortality of patients with HIV and tuberculosis admitted to resuscitation area of an urban district-level hospital in Cape Town - Swarts, Lynne (Stellenbosch : Stellenbosch University, 2020)
Thesis (MFamMed)--Stellenbosch University, 2020.